A COMPARATIVE STUDY OF THE PROXIMATE COMPOSITION OF MALE AND FEMALE YELLOWFIN TUNA (THUNNUS ALBACARES) OFF THE VISAKHAPATNAM COAST, INDIA - K, Lakshmi Kantamma; M, Ratna Raju (International Journal of Zoology, Environment and Life Sciences, 2026)
The present study evaluates and compares the proximate composition of muscle tissue in male and female yellowfin tuna (Thunnus albacares) collected from the Visakhapatnam coast, eastern India. Biochemical constituents such as moisture, protein, lipid, and carbohydrate were analyzed using standard analytical methods. Results revealed noticeable sex-based variations in muscle composition. Female tuna exhibited marginally higher lipid and moisture content, whereas male tuna showed relatively higher protein concentration. Carbohydrate content remained low and comparable in both sexes. These differences are attributed to physiological and reproductive energy allocation patterns. The findings highlight the importance of sex-based nutritional assessment for fisheries management, processing strategies, and value-added product development.